2010
DOI: 10.1016/j.ab.2010.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Development of a noncompetitive phage anti-immunocomplex assay for brominated diphenyl ether 47

Abstract: We present a new application of the noncompetitive phage anti-immunocomplex assay (PHAIA) by converting an existing competitive assay to a versatile noncompetitive sandwich-type format using immunocomplex binding phage-borne peptides to detect the brominated flame retardant, brominated diphenyl ether 47 (BDE 47). Three phage-displayed 9-mer disulfide-constrained peptides that recognize the BDE 47-polyclonal antibody immunocomplex were isolated. The resulting PHAIAs showed variable sensitivities, and the most s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…However, once these specific antibodies have been prepared, these methods can easily be standardized. The recently developed phage display technology is a powerful and reliable technique for generating antibodies, and has successfully been applied to the preparation of anti-idiotype antibody (Goletz et al, 2002;Zhang et al, 2002;Raats et al, 2003;Coelho et al, 2004;Tometta et al, 2007) and anti-metatype antibody (Kim et al, 2009;Kim et al, 2010). Also, a phage display technology-based "split-Fv system" has recently been developed to rapidly evaluate and select antibody variable region (Fv) fragments that are suitable to open sandwich immunoassay (Aburatani et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…However, once these specific antibodies have been prepared, these methods can easily be standardized. The recently developed phage display technology is a powerful and reliable technique for generating antibodies, and has successfully been applied to the preparation of anti-idiotype antibody (Goletz et al, 2002;Zhang et al, 2002;Raats et al, 2003;Coelho et al, 2004;Tometta et al, 2007) and anti-metatype antibody (Kim et al, 2009;Kim et al, 2010). Also, a phage display technology-based "split-Fv system" has recently been developed to rapidly evaluate and select antibody variable region (Fv) fragments that are suitable to open sandwich immunoassay (Aburatani et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The noncompetitive phage ELISA using the phage clone selected from plate #2 was performed according to the method reported by Kim et al [2]. Again, the half-maximum signal enhancement concentration (EC 50 ) and the LOD (EC 10 ) were obtained from the four-parameter logistic calibration curve of a noncompetitive assay.…”
Section: Phage Elisasmentioning
confidence: 99%
“…2,2′,4,4′-Tetrabromodiphenyl ether (BDE47) is one of the most ubiquitous and toxic congeners in the environment and can be an indicator of exposure to lower brominated PBDEs, and so was selected as the target analyte for immunoassay development [1]. Kim et al [2] have recently reported the selection of a polyclonal antibody-BDE47 immunocomplex binding peptides and the development of a sensitive noncompetitive assay for BDE47.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phage display technique offers attractive materials to develop alternate immunoassays that may enhance assay performance by increasing sensitivity and selectivity [8]. Phage-displayed peptide libraries have been a powerful tool for isolating peptides that specifically bind to analyte-free antibodies (peptidomimetics) or analyte-bound antibodies (anti-immunocomplex peptides) [9].…”
Section: Introductionmentioning
confidence: 99%